2008
DOI: 10.1111/j.1524-4741.2007.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Variation by Insurance Status for Breast Cancer Patients

Abstract: Few studies have examined the relationship of insurance status with the presentation and treatment of breast cancer. Using a state cancer registry, we compared tumor presentation and surgical treatments at presentation by insurance status (private insurance, Medicare, Medicaid, or uninsured). Student's t-test, Chi-square test, and ANOVA were used for comparison. P-values reflect a comparison to insured patients. From 1996 to 2005, there were 6876 cases of invasive breast cancer with either private (n = 3975), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
74
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 31 publications
13
74
1
Order By: Relevance
“…These findings, along with the regressionbased suggestion that breast cancer care-survival relationships are largely mediated by income extremes in the United States, but not in Canada seem to most parsimoniously indict inadequate health insurance coverage among America's extremely poor. In fact, this study's findings seem extraordinarily convergent with US studies that have consistently observed strong relationships between low-income, various under-and uninsured statuses, and relatively later stage at breast cancer diagnosis, lack of treatment access and early death (Anderson and Eamon, 2005;Chen et al, 2008a;Coburn et al, 2008;Griggs et al, 2007;Hahn et al, 2007;Purc-Stephenson and Gorey, 2008;Studts et al, 2006;Ward et al, 2008). It is likely that the differential outcomes this study observed will persist until medical coverage and the best available care is made available to all Americans with cancer (Freedman, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…These findings, along with the regressionbased suggestion that breast cancer care-survival relationships are largely mediated by income extremes in the United States, but not in Canada seem to most parsimoniously indict inadequate health insurance coverage among America's extremely poor. In fact, this study's findings seem extraordinarily convergent with US studies that have consistently observed strong relationships between low-income, various under-and uninsured statuses, and relatively later stage at breast cancer diagnosis, lack of treatment access and early death (Anderson and Eamon, 2005;Chen et al, 2008a;Coburn et al, 2008;Griggs et al, 2007;Hahn et al, 2007;Purc-Stephenson and Gorey, 2008;Studts et al, 2006;Ward et al, 2008). It is likely that the differential outcomes this study observed will persist until medical coverage and the best available care is made available to all Americans with cancer (Freedman, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…While a very modest to null association between SES and breast cancer survival has been observed in Canada where necessary medical care is universally covered. [18][19][20] Critical betweencountry comparisons have also been consistent with the health insurance explanation, 21,22 demonstrating particular Canadian survival advantages among residents of the lowest income areas. 18,19 Consistent with this well known international SES-breast cancer survival pattern, we hypothesized the following: (1) Within-country: Wait times for initial surgery and adjuvant RT would be associated with SES in the US (lower SES would wait longer), but not in Canada.…”
mentioning
confidence: 49%
“…Some authors suggest that cost savings could be gained by performing these complex procedures only at high-volume centers, which have decreased hospital charges both in the setting of reconstruction complications and without, a finding recently identified by Albornoz et al 15 in regard to immediate autologous breast reconstruction. One of the interesting findings of this study is insurance coverage trends for patients undergoing DIEP f laps; these patients 25 but it is perhaps surprising that the type of reconstruction the patient receives is correlated with insurance status. It should be noted that, if more than 1 payer is listed for a hospital discharge, only the first-listed payer is reported in the HCUP NIS for classifying insurance status; this may overestimate or underestimate insurance coverage for this cohort.…”
Section: Discussionmentioning
confidence: 91%